2021
DOI: 10.1016/j.aninu.2020.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary sodium butyrate on growth, digestive enzymes, body composition and nutrient retention-related gene expression of juvenile yellow catfish (Pelteobagrus fulvidraco)

Abstract: An 8-week feeding trial was conducted to evaluate the effects of sodium butyrate (SB) on growth, digestive enzymes, body composition and nutrient retention-related gene expression of juvenile yellow catfish ( Pelteobagrus fulvidraco ). Five isonitrogenous and isolipidic diets (420 g/kg protein and 90 g/kg lipid) were formulated to contain 0 (control), 250, 500, 1,000 or 2,000 mg/kg SB. Triplicate groups of 40 fish (BW = 1.26 ± 0.01 g) per tank (300-L cylindrical fiberglass tanks) for eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 60 publications
2
11
0
Order By: Relevance
“…The term "digestive enzymes" has been used to refer to enzymes which can enhance nutrient digestion and absorption. High-digestive enzyme activities could promote nutrition digestion and absorption, thereby affecting growth performance directly [28,29]. Research showed that the activities of digestive enzymes (lipase, protease, and amylase) in aquatic animals could be affected by diet formula [28,30].…”
Section: Discussionmentioning
confidence: 99%
“…The term "digestive enzymes" has been used to refer to enzymes which can enhance nutrient digestion and absorption. High-digestive enzyme activities could promote nutrition digestion and absorption, thereby affecting growth performance directly [28,29]. Research showed that the activities of digestive enzymes (lipase, protease, and amylase) in aquatic animals could be affected by diet formula [28,30].…”
Section: Discussionmentioning
confidence: 99%
“…We found that appropriate supplementation of tributyrin promoted the growth of grass carp, and the 100% survival rate demonstrated that the tributyrin supplemental concentrations we used in this study showed no toxicity to the fish. These suggested that tributyrin had a similar function as that of sodium butyrate on the growth of fish [ 8 , 9 ]. In this study, although the SGR of moderate tributyrin supplementation groups was promoted significantly compared with the control groups, it was still obviously lower than those of several previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Butyrate and its salts as feed additives have been found to play important roles in intestinal nutrient absorption and health and were considered as a potential substitute of antibiotic feed additives [ 4 , 5 , 6 , 7 ]. In terms of aquatic animals, appropriate levels of sodium butyrate can be a desirable growth promoter to stimulate growth and nutrient retention in juvenile yellow catfish [ 8 ]. Sodium butyrate combined with lippia origanoide essential oil supplemented in the commercial diet of Nile tilapia juveniles can reduce the concentration of total heterotrophic bacteria in the intestine [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in rice field eel (Monopterus albus), the digestive enzyme activities were not affected by dietary sodium butyrate [37]. The different results may be associated with the forms and concentrations of sodium butyrate, the structure of digestive organs, and the experimental environment [36]. 8 Aquaculture Nutrition epithelial cells and intestinal histology play important roles the digestion and absorption of nutrients [38].…”
Section: Effect Of Dietary Fishmeal and Sodium Butyrate On Thementioning
confidence: 99%